Computational Substrates of Social Norm Enforcement by Unaffected Third Parties - Zhong, Songfa (Neuroimage, 2016)
Enforcement of social norms by impartial bystanders in the human species reveals a possibly unique capacity to sense and to enforce norms from a third party perspective. Such behavior, however, cannot be accounted by current computational models based on an egocentric notion of norms. Here, using a combination of model-based fMRI and third party punishment games, we show that brain regions previously implicated in egocentric norm enforcement critically extend to the important case of norm enforcement by unaffected third parties. Specifically, we found that responses in the ACC and insula cortex were positively associated with detection of distributional inequity, while those in the anterior DLPFC were associated with assessment of intentionality to the violator. Moreover, during sanction decisions, the subjective value of sanctions modulated activity in both vmPFC and rTPJ. These results shed light on the neurocomputational underpinnings of third party punishment and evolutionary origin of human norm enforcement.